Diversidade de rizóbios em pastagens de Brachiaria decumbens - TERRA, Ana Beatriz Carvalho (2018)
Along with the increase in the world's population is its growing demand for food, requiring that the agricultural sector develop management techniques that not only favor productivity but also reduce costs and environmental impacts from production. Much of Brazil's pasture area is in a state of degradation, being unable to supply the productivity required by the animals. Therefore, the use of forage legumes has gained prominence as an alternative to allow a diet rich in proteins to animals, and to reduce costs with nitrogen fertilizers, which are mostly imported and have the potential to pollute water courses and contribute to the greenhouse effect. The legumes can establish interactions with soil microorganisms, called diazotrophic, which can be free living, associative, or symbiotic, that have the capacity to reduce atmospheric nitrogen (N2) to ammonia (NH3) and to provide this nutrient to the plants by a process called biological nitrogen fixation (BNF). These microorganisms are also capable of promoting plant growth through various processes, such as the production of growth hormones. The synergism between symbiotic and associative bacteria has been studied, through coinoculation techniques, to increase crop production. The objectives of this study were to evaluate the diversity of diazotrophic bacteria found in pasture soil cultivated under Brachiaria decumbens, to authenticate and evaluate the efficiency of BNF in bacterial isolates in lupine and crotalaria, and to analyze the effects of the coinoculation with the strain Azospirillum brasilense (AbV-5) in these two legume species. The research was conducted in the Laboratory of Soil Microbiology and Biochemistry and in the Experimental Sector of the José do Rosário Vellano University (UNIFENAS). Soil samples from four distinct areas were collected in the cities of Alfenas and Três Pontas (MG). The diversity of diazotrophic bacteria was evaluated by means of the morphological characterization of bacterial colonies isolated from nodules of bait plants, being estimated by the Shannon index, where it was possible to observe that forage peanut was the legume that showed the highest diversity values for all areas evaluated. The dry matter of the shoot (DMS), dry matter of the root (DMR), number of nodules (NN), nodule dry matter (DMN) and symbiotic efficiency (EFR) were used for evaluation of symbiotic efficiency and effects of coinoculation. In those analysis the isolate UNIFENAS 06-03 and UNIFENAS 05-21 showed better results for lupine and crotalaria, respectively, which presented higher values of MSPA, MSR and EFR.